STUDI FAKTOR KANSEI PADA DESAIN KEMASAN KAIN TENUN ULAP DOYO KHAS KALIMANTAN TIMUR - Dita Andansari; I Made Marthana Yusa (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2020)
Most of the SMEs Ulap Doyo woven cloth craftsmen in East Kalimantan, especially in Kutai Kartanegara and Samarinda have not provided packaging for their products. The purpose of this research is to get people's preference for Ulap Doyo woven cloth packaging. The method used is kansei engineering, a method that translates the emotion or psychological in the design of the product. The results obtained are (1) The factors that influence people's preferences in choosing Ulap Doyo woven fabric packaging products are: production / materials with a variance of 30,001%, emotional appeal with a variance of 15.298%, finishing with a variance of 12.124% and design with a variance of 11.179%. (2) kansei society of Ulap Doyo woven cloth packaging products is proud, beautiful, simple, unique, machine-printed, bold, contrast, shiny and smooth. (3) preferred design category: packaging material: thickness, shape: not an ordinary box (symmetrical), but can be a triangular prism or a modification of a box (asymmetrical box), color: dark neutral (black) and warm color physic (red) and finishing